Identifying Customers’ Barriers in Buying Sustainable Beauty Products - Peyton, Fanny; Purwanegara, Mustika Sufiati (Integrasi Sains Media, 2023)
Customers' deeper understanding of environmental issues plays a role in the swift growth of sustainable beauty enterprises. The desire of consumers to purchase sustainable beauty products have also increased, according to studies. Due to the pandemic, the sustainable beauty market is likely to rise in the next years as people strive for a healthier, more environmentally conscious lifestyle. Firms are also continually producing inventive products to satisfy the demands of their clients and to keep up with the rising competition. Researchers revealed how sustainable practices can increase brand loyalty and help firms succeed in more competitive surroundings. Other experts, on the other hand, have noted that even knowledgeable clients to environmental issues are not purchasing these sustainable products. Negative customer perceptions emerge, and it is unclear how their behavior will alter. This study uses qualitative method through thematic analysis in obtaining the data. The form of data is statements from online conversations from social media and beauty communities. This study discovered the barriers to buy from customers’ view, include the difficulty to search for suitable products for their skin, expensive price of product compared to its quality, low trust to brands, poor product quality, poor product hygiene, and bad production process management by firms. These barriers are also related to how they are more aware of green washing marketing methods. These insights would be beneficial for beauty firms who are willing to gain new target markets by emphasizing brand communication and practices that would decease customers’ concerns towards sustainable brands and lead them to product purchase. Firms could improve their product innovation to increase its performance, quality, and effectiveness to attract customers by also communicating their sustainable practices through their communication in the form of advertisements, value proposition, or product positioning. Keywords: sustainable beauty, product purchase, barriers to buy